The anterior thalamic nuclei and nucleus reuniens: So similar but so different. (December 2020) - Mathiasen, Mathias L.; O'Mara, Shane M.; Aggleton, John P.
Highlights: Despite overlapping cortical connectivity, different dorsal/ventral gradients. Common domains of function but different contributions. Primacy of anterior thalamic - retrosplenial interactions. Primacy of nucleus reuniens - frontal interactions. Contrasting patterns of hippocampal - thalamic interactivity. Abstract: Two thalamic sites are of especial significance for understanding hippocampal – diencephalic interactions: the anterior thalamic nuclei and nucleus reuniens. Both nuclei have dense, direct interconnections with the hippocampal formation, and both are directly connected with many of the same cortical and subcortical areas. These two thalamic sites also contain neurons responsive to spatial stimuli while lesions within these two same areas can disrupt spatial learning tasks that are hippocampal dependent. Despite these many similarities, closer analysis reveals important differences in the details of their connectivity and the behavioural impact of lesions in these two thalamic sites. These nuclei play qualitatively different roles that largely reflect the contrasting relative importance of their medial frontal cortex interactions (nucleus reuniens) compared with their retrosplenial, cingulate, and mammillary body interactions (anterior thalamic nuclei). While the anterior thalamic nuclei are critical for multiple aspects of hippocampal spatial encoding and performance, nucleus reuniens contributes, as required, to aid cognitive control and help select correct from competing memories.